2014
DOI: 10.1108/sampj-04-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening private certification systems through public regulation

Abstract: Purpose – Private certification systems (PCS) have emerged as governance tools for sustainable development, regulating social and environmental standards through global supply chains. PCS are seen as essentially private and market-driven, but governments have engaged with them in various ways. There are also substantial differences in the institutional design of PCS with regard to the standard-setting process, ex-ante conformity assessment and ex-post verification procedures. Consequently, what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 27 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…With the implementation of the VSS at national and local level, both stakeholders and scholars have more and more realized that these standards do not operate in isolation, but rather interact with state-based regimes and regulations [14]. Their legitimacy and effectiveness are dependent on these regimes and regulations [15,16]. Thus, the understanding of the operation of transnational private regulation requires the inclusion of the state into the analysis of VSS [2,14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…With the implementation of the VSS at national and local level, both stakeholders and scholars have more and more realized that these standards do not operate in isolation, but rather interact with state-based regimes and regulations [14]. Their legitimacy and effectiveness are dependent on these regimes and regulations [15,16]. Thus, the understanding of the operation of transnational private regulation requires the inclusion of the state into the analysis of VSS [2,14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous debates in SAMPJ have centered on voluntary sustainability reporting/ certification and the reasons for their (un)soundness, like the relevance of reporting content and format, of impact measurement, external auditing and learning. As regards private CSR standards or certification systems, prior work has shown that public regulations could and should shape and steer them toward greater effectiveness and scale (Bendell et al, 2011;D'Hollander and Marx, 2014;Bomhoff and Meuwese, 2011). We demonstrate that a private meta-governance endeavor could help with this.…”
Section: Practical Implications and Future Researchmentioning
confidence: 80%
“…There are already some examples on how this can be achieved. For example, in the case of sustainable public procurement, EU directives stipulate requirements on how social and environmental standards should be set and enforced in order to be recognized for sustainable public procurement (D'Hollander and Marx, ).…”
Section: Discussionmentioning
confidence: 99%